3D printing of CF/nylon composite mold for CF/epoxy parabolic antenna. (October 2020) - Chen, Yi; Lu, Jiang; Guo, Qing; Wan, Lei
Parabolic antennas, which are wildly used as high-gain antennas for point-to-point communications, need many iterations of design-fabrication-test in parabolic antenna development. However, traditional molding via mechanical processing takes a long manufacturing cycle and high cost. In this paper, a 3D-printed CF/nylon composite parabolic mold for CF/epoxy parabolic antenna is studied. It's found that the coefficient of thermal expansion (CTE) of 3D-printed CF/nylon composite is usually anisotropic due to the low adhesion between printed layers and the aligned short carbon fiber along the printing trace. Here an inclined mode of 3D printing could uniform the CTE of the antenna mold and solve the problems of large printing steps and the separation of supports and mold occurred in horizontal and vertical modes, respectively. The parabolic mold also reveals high profile precision with a low root mean square (RMS) deviation of 0.14 mm. Utilizing the 3D-printed CF/nylon composite mold, parabolic antenna skin with low surface RMS deviation of 0.16 mm was successfully fabricated by laying CF/epoxy prepreg and curing in autoclave. This research about isotropic and smooth 3D-printed CF/nylon mold may support the low-cost and rapid mold development for microwaves relay links on ground and satellite communication antennas.